Faktor-Faktor Yang Mempengaruhi Kepuasan Konsumen Pada Pengguna Aplikasi Jasa Gojek di Medan - Nasution, Satria Mirsya Affandy; Nasution, Asrizal Efendy (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
This study aims to determine and analyze the factors that influence consumer satisfaction on Gojek service application users in Medan. The factors studied were service quality, price, brand image and promotion factors. The approach used in this research is associative by using primary data through questionnaires and interviews. The population in this study are consumers in the city of Medan who have the Gojek application on their cellphones and have used it at least 5 times. The sampling method used probability sampling with a sample of 100 people. The data analysis technique used multiple linear regression, partial, simultaneous hypothesis testing, and looking for the coefficient of determination. The results of the study stated that the factors of service quality, price, brand image and promotion had a positive and significant influence on consumer satisfaction for Gojek service application users in Medan either partially or simultaneously.